Entre práticas populistas e crimes hediondos : uma proposta de análise a partir da teoria política de Ernesto Laclau - Ramos, Marcelo Buttelli (2016)
The purpose of this dissertation is to examine the analytical developments that can be achieve by understanding the “populism” as a theoretical category free of pejorative connotations. At first, we intend to examine the “uses” attributed to the term within a precise set of criminological approaches. The study of the criminological discourses related to the theme show, in this sense, the existence of a true discursive formation constituted around the idea that “populism”, in its punitive dimension, represents a political anomaly that tends to compromise the guaranteeing rationality of contemporary legal-penal systems. Consequently, we suggest the possibility of dispensing another analytical treatment to the term. Taking Ernesto Laclau's theory as his starting point, we considered the consequences that could be drawn from the analysis of the populist phenomenon if we accepted to understand the term as the best finished expression of a political logic that is inseparable from contemporary democratic regimes. Finally, we set out to test, from the empirical point of view, the heuristic value of the explanations conceived by the aforementioned author on the question of populism. The context of justification: the speeches fixed in the topic of the explanatory statement of the legislative proposals related to the Heinous Crimes Act and their respective reforms. At the end of the investigation, we indicate the reasons why the debate carried out by the political philosophy about the very meaning of democracy can be truly helpful in order to structure a powerful criticism, capable of contributing to the denaturalization of the belief articulated around the idea of "necessity" of punitive power.